An Intrinsic Exploratory Case Study of Parenting Children at Risk (CAR) (British Journal of Multidisciplinary and Advanced Studies, 2024)
The presence of children-at-risk (CAR) in some of the Filipino home challenges parenting. Using a case study design, this study explored select parents-beneficiaries of Pantawid Pamilyang Pilipino Program (4Ps) in Ozamiz City ways of parenting Children-at-Risk (CAR).   Purposeful sampling was employed to choose the 13 participants. Data were collected from multiple sources such as Focus Group Discussion (FGD), In-depth Interview (IDI), Key Informant Interview (KII), and material artifacts.  Trustworthiness was observed.  Reflexivity statement was written to disclose the role of the researcher. To determine the codes, categories, and themes, data were analyzed using HyperResearch software.   The findings highlight the following themes such as corrective-supportive parenting, ways of addressing CAR’s transitional struggles, and establishing open communication. From these themes, it can be inferred that parenting styles may differ from other parents because parenting children-at-risk has neither set of techniques nor gold standard.  Parents need to be skillful, creative, and be attentive listeners to the unspoken feelings and desire of their children.  Future research may be conducted to determine patterns of parenting and children’s behavior in other cities and municipalities with cases of CAR.